The Effect of Profitability, Leverage, Liquidity, Profit Efficiency on Firm Value with Dividend Policy as Moderation - Kurniawan, Iwan; Waspada, Ikaputera; Sari, Maya (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
Purpose: This study aims to analyze the effect of profitability, leverage, liquidity, on firm value with moderation of dividend policy on LQ45 issuers on the IDX. Methodology: The research approach used quantitative methods with sampling using purposive sampling of 30 issuers, the data analysis technique used moderated regression analysis (MRA). Finding: The four variables namely profitability, leverage, liquidity, dividend policy have a significant influence on firm value. However, when dividend policy is moderated, only leverage and liquidity have a significant influence on firm value. Implication: Provides knowledge insights for investors, shareholders, and regulators on matters that affect firm value and are important for financial management, provides important information on how dividend policy plays a role and can affect firm value, and how corporate authorities can develop more efficient methods to increase its value from several aspects. Originality: This research is original to the author due to the use of secondary data from the IDX on LQ-45 issuers from 2020 to 2023, innovative and integrated methodological methods, and broad practical implications. This research adds to the academic and practical literature on corporate stocks and financial management, especially developing countries such as Indonesia.